Application of 3D printing technology to left atrial appendage occlusion. (15th March 2017) - Li, Huakang; Qingyao,; Bingshen,; Shu, Maoqin; Lizhong,; Wang, Xueqin; Song, Zhiyuan
Abstract: Background: Three-dimensional printing (3DP) has undergone rapid development in medical applications. However, only a few reports have described its applications in left atrial appendage (LAA) occlusion. We assessed the feasibility and effectiveness of the 3DP technology for left atrial appendage (LAA). Methods: Forty-two patients with atrial fibrillation (average age: 69.3 ± 7.8 years) were randomly assigned to two groups equally (3DP and control). The transoesophageal echocardiography (TOE), LAA angiography, and cardiac computed tomography angiography measurements of the LAA orifice size between the groups. The procedure times, radiographic exposure, contrast agent volumes, residual shunt and costs were presented between the two groups. Results: All patients underwent a successful LAA occlusion operation with the Watchman device. TOE, LAA angiography, and cardiac computed tomography angiography measurements of the LAA orifice size between the groups were 20.4 ± 2.5 vs. 20.1 ± 3.3 mm, 19.6 ± 2.2 vs. 19.5 ± 2.8 mm, and 20.8 ± 2.1 vs. 20.2 ± 3.0 mm, respectively ( p  > 0.05). After the occlusion, the immediate TOE examination showed 3 mild residual shunt cases in the control group. The radiation exposure was significantly reduced in the 3DP compared with the control group ( p  < 0.05). The patients were followed for an average of 7.7 ± 2.5 months. No postoperative complications, device-related thrombosis, or ischemic events occurred. Conclusions: LAA occlusion guided by 3DP technology is feasible. 3DP increases the working efficiency and ensures the effectiveness of occlusion, making it valuable for clinical application.